STUDI PERBANDINGAN KANDUNGAN NUTRIEN DAGING BABI BALI DENGAN BABI LANDRACE - I W. E., Suandita; Sriyani, N. L. P.; Suranjaya, I G. (Jurnal Peternakan Tropika, 2016)
The study was carried out to determine differences in nutrients content of Balinese pork with landrace pork conducted at Traditional Animal Slaughter House and Laboratory of Livestock Product Technology and Microbiology, Faculty of Animal Husbandry University of Udayana for two months. This study used a completely randomized design (CRD) using balinese pork reared traditionallyand landrace pork reared intensivelyas  treatments.The meat in the LD ( Longisimusdorsi ) musclesfrom these pigs of both breeds was taken as a sample. The variables measured were the levels of protein, fat, carbohydrates, moisture and ash content. The data were obtained and analyzed by Two Independent Sample T-test. The results showed that protein and carbohydrate of landrace pork were significantly (P<0.05) higher than balinesepork. The fat content of balinesepork was significantly (P<0.05) higher than landrace pork, Overthere moisture and ash content of balineseand landrace porkmeat were not significantly different. The results of this study concluded that the nutrients content of landrace pork were better than the nutrients content of balinesepork because it had higher protein and carbohydrates, as well as having a lower fat content than balinese pork.
Keywords: nutrients, pork, balinese pork, landrace pork